A cross-sectional study on Iraqi patients with COVID-19 and a description of pulmonary complications (Eurasian Medical Research Periodical, 2022)
This study aims to find out the effect of COVID-19 and a description of pulmonary complications. Where a cross-sectional study was conducted from several different hospitals for a period of 6 months (12-4-2020 to 10-1-2020), and this study was designed by relying on a questionnaire distributed to patients to find out the pulmonary complications, then the data and demographic information related to the patients were analyzed by relying on the statistical analysis program IBM SOFT SPSS 22, where statistical tools were used to know the quality of the relationship with Covid patients, in addition to knowing the logistic analysis to analyze risk factors for patients The results that were found in this study are the collection of 200 patients aged between 20-60 years, and the patients were distributed according to gender (Male 112 with 56% and females 88 patients with 44%), comorbidities were found and were the most Frequent in this study is diabetes for 44 patients and heart disease for 43 patients, HYPERTENSION for 50 patients.